2014
DOI: 10.1186/1756-0500-7-590
|View full text |Cite
|
Sign up to set email alerts
|

Culture and affect: the factor structure of the affective style questionnaire and its relation with depression and anxiety among Japanese

Abstract: BackgroundAffective styles are assumed to be one of the underlying processes of depression and anxiety maintenance. However, little is known about the effect of depression and anxiety and the cultural influence of the factor structure. Here, we examined the cross-cultural validity of the Affective Style Questionnaire and its incremental validity for the influence on depression and anxiety.MethodsAffective Style Questionnaire was translated into Japanese using standard back-translation procedure. Japanese unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
4
19
0
1
Order By: Relevance
“…The factor correlations were high and significant (Table 3 ), ranging from 0.57 between Adjusting and Concealing to 0.93 between Tolerating and Adjusting. We also performed an ICM-CFA of the Japanese four-factor model ( Ito & Hofmann, 2014 ), which resulted in slightly better fit statistics than the three-factor model, but the overall model fit was still poor: χ 2 (98) = 1626.025, p < 0.001; CFI = 0.849; TLI = 0.815; RMSEA = 0.099 [0.094, 0.103]. When CFA-models fit the data this poorly, it is common practice to examine the modification indices and to relax the restrictive CFA-constraints by allowing for cross-loadings and item correlations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The factor correlations were high and significant (Table 3 ), ranging from 0.57 between Adjusting and Concealing to 0.93 between Tolerating and Adjusting. We also performed an ICM-CFA of the Japanese four-factor model ( Ito & Hofmann, 2014 ), which resulted in slightly better fit statistics than the three-factor model, but the overall model fit was still poor: χ 2 (98) = 1626.025, p < 0.001; CFI = 0.849; TLI = 0.815; RMSEA = 0.099 [0.094, 0.103]. When CFA-models fit the data this poorly, it is common practice to examine the modification indices and to relax the restrictive CFA-constraints by allowing for cross-loadings and item correlations.…”
Section: Resultsmentioning
confidence: 99%
“…In an independent clusters model-CFA (ICM-CFA), each item is allowed to load on one factor, in this case the respective subscale, and all other factor loadings are constrained to be zero. This procedure was used in the Japanese study ( Ito & Hofmann, 2014 ). However, Asparouhov, Muthén, and Muthén ( 2009 ) and Marsh and colleagues ( 2009 ) have argued that because of its use of a strict measurement model, CFA has a number of disadvantages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations with positive affect and reappraisal, which is related to greater experience of positive emotion (Gross & John, ), reflected that the PEIDS included the ability to access positive emotion in a distressed state. The correlation with the ASQ adjusting subscale also indicated that the PEIDS had one aspect of response modulation: assessing the ability to modulate the emotional experience and expression in response to the demands of a given context (Hofmann & Kashdan, ; Ito & Hofmann, ). In line with our expectations, associations between the PEIDS and ASQ concealing, holding, and tolerating; ERQ suppression; RRQ‐S rumination and reflection; and PANAS negative affect schedule ranged in magnitude from small to medium.…”
Section: Discussionmentioning
confidence: 99%
“…The items are measured on a five‐point Likert scale. The reliability and validity of the ASQ has been demonstrated with a sample of Japanese participants (Ito & Hofmann, ). Confirmatory factor analysis confirmed a four‐factor structure and added a new factor, holding the emotion, to original factors in a Japanese sample (Ito & Hofmann, ).…”
Section: Methodsmentioning
confidence: 99%